TJNPR 2019
DOI: 10.26538/tjnpr/v3i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Psychopharmacolgical Acitivities of Ethanol Leaf Extract of Saccharum officinarum

Abstract: Saccharum officinarum L. (Poaceae) is used in Ibibio ethnomedicine for the treatment of various diseases such as CNS disorders. The ethanol leaf extract of Saccharum officinarum (170, 340 and 510 mg/kg) was investigated for antidepressant and anticonvulsant activities in Swiss albino mice (20-25 g). Open field, force swimming and tail suspension tests were used to assess antidepressant activity, while pentylenetetrazol and aminophylline-induced convulsion models were used to assess anticonvulsant activity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Biological activities reported on the leaf include antibacterial and anthelmintic (Palaksha et al, 2013), antihyperglycaemic, anti-hyperlipidaemic (Ojewunmi et al, 2013), antioxidant (Ojewunmi et al, 2013;Sun et al, 2014). Diuretic and antiurolithiatic (Palaksha et al, 2015), antidepressant and anticonvulsant (Okokon et al, 2019), analgesic (Okokon et al, 2021) and antimalarial (Okokon et al, 2022) activities.…”
Section: Saccharum Officinarummentioning
confidence: 99%
“…Biological activities reported on the leaf include antibacterial and anthelmintic (Palaksha et al, 2013), antihyperglycaemic, anti-hyperlipidaemic (Ojewunmi et al, 2013), antioxidant (Ojewunmi et al, 2013;Sun et al, 2014). Diuretic and antiurolithiatic (Palaksha et al, 2015), antidepressant and anticonvulsant (Okokon et al, 2019), analgesic (Okokon et al, 2021) and antimalarial (Okokon et al, 2022) activities.…”
Section: Saccharum Officinarummentioning
confidence: 99%
“…Panicum maximum Jacq (Poacace) is a perennial grass which is distributed widely in Africa and other tropical regions of the world (Van Oudtshoorn, 1999) Antidiabetic (Antia et al, 2010), antimalarial and analgesic (Okokon et al, 2012), antibacterial (Gothandam et al, 2010;Doss et al, 2011a;Doss et al, 2011b), antiinflammatory and antipyretic (Okokon et al, 2011), antifungal (Kanife, 2012), anticancer, antioxidative burst and antileishmanial (Okokon et al, 2014) activities of the leaf extract have been reported. Also, Panicum maximum root extract has been reported to possess analgesic and antimalarial…”
Section: Introductionmentioning
confidence: 99%
“…properties (Okokon et al, 2016) with LD50 value of 2738.1 mg/kg, antidepressant and anticonvulsant (Okokon et al, 2018) and anti-inflammatory activities (Udobang et al, 2020) and antiulcerogenic (Okokon et al, 2021). Phytochemical constituents of the root such as alkaloid, flavonoid, tannins, terpenes, saponin, and cardiac glycosides (Okokon et al, 2016) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…SAABMAL, an ethnomedicinal polyherbal formulation containing S. officinarum, is used in Nigeria to treat uncomplicated malaria infection 14 . The reported biological activities of the leaf extracts also include anti-hyperglycaemic, anti-hyperlipidaemic, antioxidant 15 , 16 , antidepressant and anticonvulsant 17 , as well as analgesic 18 activities. Phytochemical investigation of sugarcane juice, and other plant parts, disclosed the presence of long-chain alcohols and acids, glycosides, phytosterols, saponins, tannins, and flavonoids 13 , 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%